PENGARUH KOMPONEN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Monica Pratiwi Lukas; Oktavianus Pasoloran; Robert Jao (AJAR, 2018)
This research aims to examine the influence of value added capital employed, value added human capital, structural capital value added and relation capital value added on firm value. The population used in this research are all banking companies listed on the Indonesia Stock Exchange with the research period 2014-2017. The method of determining the sample using purposive sampling with certain criteria and using secondary data so that only 21 companies were selected to used being sample. The method of analysis used double linear regression analysis. The result show that value added capital employed has positive correlation and significant effect on firm value. The research also found that value added human capital, structural capital value added, and value added relation capital has positive correlation but no significant effect on firm value. First implications from this research is the company can survive from competitive business competition to sustainability of the company. Second implications from this reseacrh is investors better invest on the company which focus on resources based view.